PEMAKAIAN BAHASA INDONESIA (KATA) DALAM SURAT RESMI/DINAS KELUAR DESA KESIMAN KERTALANGU KECAMATAN DENPASAR TIMUR DENPASAR (STUDI KASUS) - I Nengah Mileh (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2019)
[The Use of Indonesian Language (Word) in the Official Letter / Outgoing Mail of Kesiman Kertalagu Village, East Denpasar Sub District, Denpasar] This research entitled "The Use of Indonesian Language (Word) in the Official Letter / Outgoing Mail of Kesiman Kertalangu Village, East Denpasar Sub District, Denpasar". The use of Indonesian, especially the use of the word in the official / official letter out of Kesiman Kertalangu Village, Denpasar Timur Sub-district, Denpasar, still found some errors. In this study, which is the object of study, namely regarding the misuse of the word. Observation methods and note-taking techniques are used in data collection, descriptive synchronic qualitative methods are used to analyze data aided by inductive or deductive techniques, while informal methods are used to present results. In this study found several types of word usage errors. The types of word usage errors include: 1) preposition writing, 2) hypercorrect word writing, and 3) improper use of words.